Globalization and Local Procurement: A Study of Supply Chain Dynamics in Australia and Bangladesh - Habib, Ahsan (Global Journal of Purchasing and Procurement Management, 2024)
Purpose: The aim of the study was to analyze the globalization and local procurement: a study of supply chain dynamics in Australia and Bangladesh. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study on strategic sourcing's impact on cost reduction in Australia and Bangladesh manufacturing firms demonstrated significant positive results. It showed that strategic sourcing led to notable reductions in procurement costs, enhanced supplier management, negotiation, and risk mitigation strategies. The findings underscored the importance of aligning procurement strategies with organizational goals for sustainable cost reductions and competitive advantages in the sector. Unique Contribution to Theory, Practice and Policy: Resource dependence theory (RDT), transaction cost economics (TCE) & institutional theory may be used to anchor future studies on analyze the globalization and local procurement: a study of supply chain dynamics in Australia and Bangladesh. Businesses in both Australia and Bangladesh should prioritize building strong relationships with local suppliers to enhance supply chain resilience. Policymakers in both Australia and Bangladesh should create supportive regulatory frameworks that promote local procurement practices.